Intensive treatment strategies in advanced-stage Hodgkin's lymphoma (HD9 and HD12): analysis of long-term survival in two randomised trials. Issue 10 (October 2018) - von Tresckow, Bastian; Kreissl, Stefanie; Goergen, Helen; Bröckelmann, Paul J; Pabst, Thomas; Fridrik, Michael; Rummel, Mathias; Jung, Wolfram; Thiemer, Julia; Sasse, Stephanie; Bürkle, Carolin; Baues, Christian; et al.
Summary: Background: Although intensified chemotherapy regimens have improved tumour control and survival in advanced-stage Hodgkin's lymphoma, data on the long-term sequelae are scarce. We did preplanned follow-up analyses of the German Hodgkin Study Group (GHSG) trials HD9 and HD12 to assess whether the primary results of these trials—which had shown that intensive initial therapy in advanced-stage Hodgkin's lymphoma has a beneficial effect on treatment outcomes—would continue with longer follow-up. Methods: In HD9 (Feb 1, 1993, to March 10, 1998), 1282 patients with newly diagnosed, histology-proven, advanced-stage Hodgkin's lymphoma received eight alternating cycles of COPP and ABVD (COPP/ABVD), eight cycles of bBEACOPP, or eight cycles of eBEACOPP. In HD12 (Jan 4, 1999, to Jan 13, 2003; registered withClinicalTrials.gov [NCT00265031 ]), 1670 patients with newly diagnosed, histology-proven, advanced-stage Hodgkin's lymphoma received eight cycles of eBEACOPP or four cycles of eBEACOPP plus four cycles of bBEACOPP (4 + 4), plus consolidation radiotherapy to initial bulk and residual disease or no radiotherapy, to analyse two non-inferiority objectives. In both trials, randomisation was done centrally in the GHSG trial coordination centre using the minimisation method including a random component, stratified according to centre, age, stage, international prognostic score, the presence or absence of a large mediastinal mass, and bulky disease. Patients and investigators were not masked to treatment allocation. All analyses were done on the intention-to-treat principle. The primary endpoint of this follow-up analysis was progression-free survival (time from first diagnosis to progressive disease, relapse, or death from any cause or censoring at the date of last information on disease status). To assess whether long-term outcome might be impaired by long-term sequelae, we analysed overall survival and second primary malignant neoplasm incidence as key secondary endpoints. Findings: Median observation time was 141 months (IQR 101–204) in HD9 and 97 months (69–143) in HD12. For HD9 trial patients, 15-year progression-free survival was 57·0% (95% CI 50·0–64·0) for COPP/ABVD, 66·8% (61·9–71·8) for bBEACOPP, and 74·0% (69·0–79·0) for eBEACOPP, 15-year overall survival was 72·3% (95% CI 66·5–78·1), 74·5% (70·1–78·9), and 80·9% (76·7–85·0), respectively. Progression-free survival and overall survival in the eBEACOPP group remained significantly better than in the COPP/ABVD group (hazard ratio [HR] 0·53, 95% CI 0·41–0·69, p<0·0001, and 0·68, 0·50–0·93, p=0·015, respectively). The 15-year cumulative incidence of second primary malignant neoplasms was 7·2% (95% CI 3·7–10·7) after COPP/ABVD, 13·0% (9·1–16·9) after bBEACOPP, and 11·4% (7·6–15·1) after eBEACOPP. For HD12 trial patients, non-inferiority of 4 + 4 was shown, with 10-year progression-free survival of 82·6% (95% CI 79·6–85·6) for eBEACOPP and 80·6% (77·4–83·7) for 4 + 4 (HR 1·13 [0·89–1·43], within non-inferiority margin of 1·50), and 10-year overall survival of 87·3% (95% CI 84·7–89·9) and 86·8% (84·2–89·4), respectively (HR 1·02 [95% CI 0·77–1·36]). Among 555 (37%) patients with residual disease after chemotherapy, omission of radiotherapy was associated with significantly worse 10-year progression-free survival (89·7% [95% CI 85·8–93·6] radiotherapy vs 83·4% [78·2–88·5] for no radiotherapy; p=0·027) and 10-year overall survival (94·4% [91·4–97·3] vs 88·4% [83·8–93·0]; p=0·025). 10-year cumulative second primary malignant neoplasms incidence was 6·4% (95% CI 3·3–9·5) for 4 + 4 and 8·8% (5·2–12·4) for eBEACOPP. Interpretation: Long-term follow-up of HD9 and HD12 shows an ongoing benefit of intensive first-line treatment and consolidation radiotherapy to residual disease in terms of progression-free survival and overall survival. Our results support the use of eBEACOPP in advanced-stage Hodgkin's lymphoma. However, because late toxicities such as second primary malignant neoplasms contribute to mortality, less toxic but equally effective treatments need to be developed to further improve overall survival. Funding: Deutsche Krebshilfe e.V.